Feasibility Study of a Citronella Oil Bioadditive Enterprise: Transforming PT Arutmin Indonesia Kintap Mine’s CSR Program into an Independent Business Unit - Ika Ila Nurhuddah; Eko Budi Santoso (International Journal Labs, 2026)
The energy sector in Indonesia remains heavily dependent on coal, which contributes significantly to greenhouse gas (GHG) emissions. Amid global efforts toward energy transition and climate change mitigation, extractive industries, including mining companies, are encouraged to improve operational efficiency, particularly in fuel utilization. This study aims to evaluate the feasibility of transforming the citronella oil bioadditive Corporate Social Responsibility (CSR) program of PT Arutmin Indonesia Kintap Mine into an independent business unit managed by BUMDesa Berkah Mulia. Using an applied qualitative research approach, this study evaluates legal, market, technical, managerial, and financial aspects, as well as sustainability impacts through Social Return on Investment (SROI) analysis. The results indicate that the business unit has promising market potential through a captive market scheme, with estimated demand exceeding 5,000 liters/month. From a technical perspective, a sustainable production target of 88 liters/month was established to achieve the operational break-even point. Financial projections based on a five-year cash flow analysis (2026–2030) under a moderate scenario demonstrated a positive Net Present Value (NPV) of IDR 24,764,518 and an Internal Rate of Return (IRR) of 10.68%. The business unit was considered feasible as a social enterprise model, with a significant social impact indicated by an SROI ratio of 2.68:1, meaning that every IDR 1 invested generated a social impact value of IDR 2.68. This study recommends establishing a Limited Liability Company (PT) structure to mitigate operational risks and implementing a minimum raw material price strategy to protect farmers.